Regulation and Function of RFRP-3 (GnIH) Neurons during Postnatal Development - Poling, Matthew C.; Kauffman, Alexander S. (Frontiers in Endocrinology, 2015)
RFamide-related peptide-3 (RFRP-3; mammalian ortholog to GnIH) potently inhibits gonadotropin secretion in mammals. Studies of RFRP-3 immunoreactivity and Rfrp expression (the gene encoding RFRP-3) in mammalian brains have uncovered several possible pathways regulating RFRP-3 neurons, shedding light on their potential role in reproduction and other processes, and pharmacological studies have probed the target sites of RFRP-3 action. Despite this, there is currently no major consensus on RFRP-3’s specific endogenous role(s) in reproductive physiology. Here we discuss the latest evidence relating to RFRP-3 neuron regulation and function during development and sexual maturation, focusing on rodents. We highlight significant changes in RFRP-3 and Rfrp expression, as well as RFRP-3 neuronal activation, during key stages of postnatal and pubertal development and also discuss recent evidence testing the requisite role of RFRP-3 receptors for normal pubertal timing and developmental LH secretion. Interestingly, some findings suggest that endogenous RFRP-3 signaling may not be necessary for the puberty timing, at least in some species, forcing new hypotheses to be generated regarding this peptide’s functional significance to sexual maturation and development.